2023
DOI: 10.3390/pharmaceutics15010242
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Hydroxyapatite/PLGA Mixed Scaffolds as a Tool for Drug Development and to Study Metastatic Prostate Cancer in the Bone

Abstract: (1) Background: Three-dimensional (3D) in vitro, biorelevant culture models that recapitulate cancer progression can help elucidate physio-pathological disease cues and enhance the screening of more effective therapies. Insufficient research has been conducted to generate in vitro 3D models to replicate the spread of prostate cancer to the bone, a key metastatic site of the disease, and to understand the interplay between the key cell players. In this study, we aim to investigate PLGA and nano-hydroxyapatite (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…In a recent work, 3D PLGA and nanohydroxyapatite were fabricated using electro-spraying, compacting, and foaming techniques. These scaffolds were used to evaluate drug toxicity and PC3 cells’ proliferation in bone-like environments [ 112 ]. Researchers have also impregnated curcumin into poly(lactic-co-glycolic) acid (PLGA) scaffolds [ 113 ].…”
Section: Cancer Metastasis 3d In Vitro Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent work, 3D PLGA and nanohydroxyapatite were fabricated using electro-spraying, compacting, and foaming techniques. These scaffolds were used to evaluate drug toxicity and PC3 cells’ proliferation in bone-like environments [ 112 ]. Researchers have also impregnated curcumin into poly(lactic-co-glycolic) acid (PLGA) scaffolds [ 113 ].…”
Section: Cancer Metastasis 3d In Vitro Modelsmentioning
confidence: 99%
“…Table 2 summarizes the various polymeric, composite, and biological materials that are used in the development of tissue-engineered scaffolds to mimic the bone site of prostate cancer metastasis. PLA-PLGA PLGA and nanohydroxyapatite scaffolds PC3 [112] Curcumin-impregnated poly(lactic-co-glycolic) acid (PLGA) scaffolds [113] PEG Polyethylene glycol hydrogel PCa and LNCaP [114] Scaffolds fabricated with poly(ethylene glycol)-fibrinogen matrix supplemented with poly(ethylene glycol)-diacrylate PC3 with BJ-5ta fibroblasts [115] One of the early studies reported the development of a three-dimensional type I collagen gel cell culture system with co-culture of human MG-63 osteoblast-like cells with highly metastatic human PC3 prostate cancer cells. This model was used to study the pathophysiology of prostate cancer at the bone [97].…”
Section: Prostate Cancer Metastasis Modelsmentioning
confidence: 99%
“…In a recent study by Dozzo et al [94], 3D scaffolds of nano-hydroxyapatite (nHA)/PLGA were developed to evaluate the effect of scaffold composition on the metastatic potential of prostate cancer cells in the bone. The presence of nHA in the 3D scaffolds highly affected the mechanical properties resulting in weaker structures, and the degradation behavior promoting cell viability.…”
Section: Other Cancer Typesmentioning
confidence: 99%
“…Finally, an important feature to investigate during PC development and metastasis is the spread of PC to the bone [ 196 ]. PC most often metastasizes to the bone, and this is the primary cause of PC-related morbidity and mortality [ 197 ].…”
Section: Standard and Novel Therapies Used In 3d Models Of Pcmentioning
confidence: 99%